On The Probability of Response of a Linear Oscillator to a Random Pulse Train - Iwankiewicz, R. (Engineering Transactions, 1989)
Dynamic response of a linear oscillator to a Poisson-distributed train of general pulses is considered. The complete expansion for the one-dimensional probability density function of the response is presented in explicit form. The coefficients of skewness and of excess are evaluated for the steady-state response to a stationary train of square pulses and their behaviour is analyzed. The truncated serics is used to examine approximately the probability density function of the stationary response. The effect of the pulse duration and of the expected rate of pulses occurrence on the approximate probability density is discussed. Positive skewness and the departure of the response probability density from the Gaussian behaviour arc explained.